1994
DOI: 10.1002/j.1460-2075.1994.tb06840.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulvomycin-resistant mutants of E.coli elongation factor Tu.

Abstract: This paper reports the generation of Escherichia coli mutants resistant to pulvomycin. Together with targeted mutagenesis of the tufA gene, conditions were found to overcome membrane impermeability, thereby allowing the selection of three mutants harbouring elongation factor (EF)‐Tu Arg230‐‐>Cys, Arg333‐‐>Cys or Thr334‐‐>Ala which confer pulvomycin resistance. These mutations are clustered in the three‐domain junction interface of the crystal structure of the GTP form of Thermus thermophilus EF‐Tu. This result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…GDP contributes to the inhibition of protein synthesis. In agreement with this is the recently presented study by Zeef et al (1994), in which it is shown that the pulvomycin-resistant mutant…”
Section: Gtpsupporting
confidence: 88%
See 1 more Smart Citation
“…GDP contributes to the inhibition of protein synthesis. In agreement with this is the recently presented study by Zeef et al (1994), in which it is shown that the pulvomycin-resistant mutant…”
Section: Gtpsupporting
confidence: 88%
“…Crystallographic studies (Hilgenfeld, R., unpublished results ; Zeef et al, 1994) have shown that Arg230 and Arg233 are part of the interface between the three domains.…”
Section: Gtpmentioning
confidence: 99%
“…Domain III of EF-Tu has been shown to be necessary for pulvomycin binding, leading to the speculation that the binding site of pulvomycin lies at the domain II-III interface [84]. A striking difference between pulvomycin and GE2770A relates to their resistance phenotype; pulvomycin sensitivity was found to be dominant to resistance [96], whereas in contrast GE2770A resistance was dominant over sensitivity [97,98]. This suggests that in the case of pulvomycin an additional mechanism must be operating other than simply limiting the availability of active ternary complex.…”
Section: Inhibition Of Ternary Complex Formation: Pulvomycin and Ge2270amentioning
confidence: 99%
“…As a result, EF-Tu is prevented from delivering aa-tRNA to the ribosomal A site. Unexpectedly, however, pulvomycin sensitivity was found to be phenotypically dominant over resistance [25], suggesting that substrate limitation alone cannot be the exact mode of inhibition. Further research may be required to clarify these discrepancies.…”
Section: Pulvomycinmentioning
confidence: 97%
“…stimulation of the replacement of GDP with GTP (Table 1), one can envisage the actions of pulvomycin as resembling those of the nucleotide-exchange factor, EF-Ts [24][25][26]. Like kirromycin, pulvomycin stimulates the GTPase activity of EF-Tu*GTP, although to a weaker extent [1].…”
Section: Pulvomycinmentioning
confidence: 99%